2016
DOI: 10.5114/aoms.2015.55675
|View full text |Cite
|
Sign up to set email alerts
|

The effect of small intestinal bacterial overgrowth on minimal hepatic encephalopathy in patients with cirrhosis

Abstract: IntroductionThe aim of the study was to investigate the significance of factors associated with minimal hepatic encephalopathy (MHE) in cirrhotic patients.Material and methodsBetween September 2012 and August 2013, 60 cirrhotic patients, including MHE and non-MHE (NMHE) patients, were included in the study. Associated factors and clinical factors were analyzed to see if they were significantly different between MHE and non-MHE patients. Upon identifying the factors showing differences, we applied multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…We also observed differences in the duodenal microbiome according to the presence of HE, which is typically a late complication of cirrhosis. Although prior studies have shown that small intestinal bacterial overgrowth is associated with HE, we additionally found that patients with HE also have lower microbial richness and diversity in the duodenum compared to patients without HE . Potentially related to this observation are prior reports that have linked lower diversity of the fecal microbiome to cirrhosis severity .…”
Section: Discussioncontrasting
confidence: 53%
“…We also observed differences in the duodenal microbiome according to the presence of HE, which is typically a late complication of cirrhosis. Although prior studies have shown that small intestinal bacterial overgrowth is associated with HE, we additionally found that patients with HE also have lower microbial richness and diversity in the duodenum compared to patients without HE . Potentially related to this observation are prior reports that have linked lower diversity of the fecal microbiome to cirrhosis severity .…”
Section: Discussioncontrasting
confidence: 53%
“…As described earlier, SIBO is commonly associated with cirrhosis, affecting up to 59% of these patients [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The gold standard diagnostic method is a demonstration of greater than 10 5 colony forming units per millimeter in the proximal jejunum via aspiration during endoscopic examination.…”
Section: Changes To Gut Microbiota In Cirrhosis and Hepatic Encephmentioning
confidence: 99%
“…SIBO typically shows an over-abundance of gram-negative bacteria including Escherichia coli and Klebsiella pneumoniae [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. These organisms are linked to the development of decompensated cirrhosis and the development of HE due to their ability to translocate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. One meta-analysis demonstrated that the prevalence of SIBO in cirrhosis is significantly greater than its prevalence in otherwise healthy individuals [ 58 ].…”
Section: Changes To Gut Microbiota In Cirrhosis and Hepatic Encephmentioning
confidence: 99%
“…Increased intestinal permeability may help bacteria move into the systemic circulation. SIBO has been implicated as an important risk factor in the etiology of both SBP and HE in LC patients [ 102 , 103 ]. Thus, SIBO is deeply involved in the progression of CLD, which may be linked to sarcopenia [ 102 , 103 ].…”
Section: Small Intestine Bacterial Overgrowth In Liver Cirrhosismentioning
confidence: 99%